AGUNAN YANG DIAMBIL ALIH : SEBUAH MEKANISME DALAM PENYELESAIAN KREDIT MACET - Dilapanga, Nur Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Credit is the provision of money or an equivalent claim based on a loan agreement between the bank and another party which requires the borrower to repay the debt after a certain period of time with interest .In the process, it is possible that the borrower is negligent in carrying out his obligations, namely that there are arrears, both principal and interest installments that exceed the specified period. Foreclosed Collateral is a method used by a bank to resolve its default on the credit. The purpose of this study is to determine the mechanism of Foreclosed Collateral as a way of solving bad credit problems. The research method used is normative, using secondary data, which is obtained from literature research, including primary, secondary and tertiary sources of law. Foreclosed Collateral can be made when credit is included in the bad category. The mechanism for setting bad credit through Foreclosed Collateral is carried out in seceral stages, including observation and revaluation of the collateral in which credit Is bad, an agreement is made between the collateral owner and the bank to transfer the collateral with sale and purchase agreement and power to sell, the guarantee is sold by the bank to another paries either under hand or auction.